Immunohistochemical localisation of androgen receptor in apocrine metaplasia and apocrine adenosis of the breast: relation to oestrogen and progesterone receptors. Issue 11 (1st November 1999) - Selim, A G; Wells, C A
Abstract : AIM: To investigate the receptor status of the sex steroid hormones in apocrine metaplasia of the breast. METHODS: 82 cases of apocrine metaplasia, including 18 of the rare lesion apocrine adenosis, were studied immunohistochemically for the expression of androgen receptor, oestrogen receptor, and progesterone receptor proteins on formalin fixed, paraffin embedded tissue sections. The standard avidin biotin complex (ABC) technique was followed and appropriate positive and negative controls were used. RESULTS: All the studied cases (82/82) were positive for androgen receptor, but were negative for oestrogen receptor and progesterone receptor. CONCLUSIONS: Apocrine metaplastic epithelium, unlike the normal breast epithelium, is responsive to androgens, through androgen receptors, rather than to the female sex hormones. This may have clinical implications.